Educating about/for food security through environmental education : an account of integration practices in teacher education programs across Ontario, Canada - Valeri, Alishia A. (Critical constructions., 2024)
This text is relevant for members of faculties of education such as administers, directors of teacher education programs, teacher educators (for pre-service and/or inservice teachers), and teacher candidates. There is also a potential appeal to professors in higher education institutions as integration practices can be adapted to meet the requirements across disciplines.K-12 classroom-based teachers may find this text useful as a source for content-based learning either from disciplinary or cross-disciplinary practice as well as individuals serving in an educational capacity in community-based settings, for instance.Parts of this work have already been presented in both US and Canadian based conferences such as the American Educational Research Association and the Canadian Society for the Study of Education and serve as optimal venues to reach the academic market. Advertising in publications geared towards providing practical articles could also serve a way to reach classroom based and community-based educators.